2023
DOI: 10.3390/su152215715
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy and Solid Waste Management: Connections from a Bibliometric Analysis

Wender Freitas Reis,
Cristiane Gomes Barreto,
Mauro Guilherme Maidana Capelari

Abstract: The aim of this study is to conduct a meta-analysis of the research published between 2012 and 2022 on solid waste management (SWM) and the circular economy (CE) using bibliometrics. To this end, the Scopus and Web of Science (WoS) databases were used as sources of publications. Processing was conducted using the R language version 4.2.2 and the Bibliometrix software package version 4.1.2. A theoretical basis was built on the terms in order to present their interactions in the context of scientific debate. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…According to Reis et al [56], the present work showed that the ongoing discourse surrounding CE and MSW is expanding, and indications strongly suggest an inherent connection between them. At the theoretical level, developing effective strategies necessitates collaboration, not only among public authorities, but also with relevant businesses, and society at large.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 62%
“…According to Reis et al [56], the present work showed that the ongoing discourse surrounding CE and MSW is expanding, and indications strongly suggest an inherent connection between them. At the theoretical level, developing effective strategies necessitates collaboration, not only among public authorities, but also with relevant businesses, and society at large.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 62%